Ingestion and digestion by the freshwater snail Pomacea canaliculata drive microplastic surface transformations and virus-mediated plastisphere functional shifts - Zhaoji Shi; Wen Zeng; Wanlin Zhuang; Fucheng Yao; Daolin Sun; Ziqiang Liu; Jiaen Zhang (Water Research, 2026)

Soil cadmium contamination facilitates the invasion of invasive weeds through enhanced herbivore resistance and competitive ability over congeneric species - Rasheed Akbar; Jianfan Sun; Chen Jin; Yanwen Bo; Amir Abdullah Khan; Nickolas Girkin; Babar Iqbal; Amjad Usman; Daolin Du (Journal of Cleaner Production, 2026)

Biochar-Seaweed Fertilizer Blend: A Multifaceted Strategy for Mitigating Nitrous Oxide Emissions, Soil Rejuvenation, and Improving Rice Crop Performance - Muhammad Aamer; Huang Guoqin; Jiaen Zhang; Hui Wei; Fahd Rasul; Daolin Sun; Wenyun Huang; Shijie Liu; Abdul Haseeb; Tahani A. Y. Asseri; Mohamed Hashem (Journal of Soil Science and Plant Nutrition, 2025)

The Effect of Native Plant Diversity on the Success of Invasive Species in Polluted Soils - Qaiser Javed; Jianfan Sun; Marko Černe; Babar Iqbal; Mohammed Bouhadi; David John Heath; Feng He; Muhammad Saif Ullah; Rasheed Akbar; Daolin Du (Ecotoxicology, 2025)

Rice-fish coculture without phosphorus addition improves phosphorus availability in paddy soil by regulating phosphorus fraction partitioning and alkaline phosphomonoesterase-encoding bacterial community - Xing LIU; Yuting CHEN; Hongjun ZHENG; Daolin SUN; Jiaen ZHANG; Qi JIA; Qi CHEN (Pedosphere, 2025)

Remediation of microplastics-contaminated agricultural soils by unmodified and modified biochar derived from Solidago canadensis L. - Babar Iqbal; Muhammad Junaid Nazir; Jiabao Lou; Yanjiao Wang; Eun Hea Jho; Mao Ye; Mingming Sun; Abdulkareem Raheem; Inamullah; Muhammad Sohail Memon; Guanlin Li; Xin Zhao; et al. (Process Safety and Environmental Protection, 2025)

The role of agricultural land management in modulating water-carbon interplay within dryland ecological systems - Wajid Ali Khattak; Jianfan Sun; Fawad Zaman; Abdul Jalal; Muhammad Shafiq; Sehrish Manan; Rashida Hameed; Ihtisham Khan; Irfan Ullah Khan; Khalid Ali Khan; Daolin Du (Agriculture, Ecosystems & Environment, 2025)

A comparative analysis of ecosystem service values from various rice farming systems: A field experiment in China - Yanqiong Ye; Hui Bai; Jiaen Zhang; Daolin Sun (Ecosystem Services, 2024)

Microbial-assistance and chelation-support techniques promoting phytoremediation under abiotic stresses - Misbah Naz; Muhammad Rahil Afzal; Shan Shan Qi; Zhicong Dai; Qiuyang Sun; Daolin Du (Chemosphere, 2024)

Carbon footprint of global rice production and consumption - Ahmed I. Abdo; Mengzhen Tian; Zhaoji Shi; Daolin Sun; Mohamed K. Abdel-Fattah; Jiaen Zhang; Hui Wei; Mohamed A. Abdeen (Journal of Cleaner Production, 2024)

Rice-fish coculture without phosphorus addition improves paddy soil nitrogen availability by shaping ammonia-oxidizing archaea and bacteria in subtropical regions of South China - Xing Liu; Daolin Sun; Huaqiao Huang; Jiaen Zhang; Hongjun Zheng; Qi Jia; Min Zhao (Science of The Total Environment, 2024)

Global Environmental Change Shifts Ecological Stoichiometry Coupling Between Plant and Soil in Early-Stage Invasions - Guangqian Ren; Miaomiao Cui; Haochen Yu; Xue Fan; Zhaoqi Zhu; Haiyan Zhang; Zhicong Dai; Jianfan Sun; Bin Yang; Daolin Du (Journal of Soil Science and Plant Nutrition, 2024)

Cadmium induced defense enhance the invasive potential of Wedelia trilobata under herbivore infestation - Mohsin Nawaz; Jianfan Sun; Yanwen Bo; Feng He; Samina Shabbir; Muhammad Umair Hassan; Linxuan Pan; Parvaiz Ahmad; Christian Sonne; Daolin Du (Journal of Hazardous Materials, 2024)

Microplastics and cadmium affect invasion success by altering complementarity and selection effects in native community - Feng He; Jianfan Sun; Justin S.H. Wan; Mohsin Nawaz; Qaiser Javed; Linxuan Pan; Wajid Ali Khattak; Yanwen Bo; Yan Xiang; Guangqian Ren; Xin Lin; Daolin Du (Science of The Total Environment, 2024)

Carbon footprint of synthetic nitrogen under staple crops: A first cradle‐to‐grave analysis - Ahmed I. Abdo; Daolin Sun; Kai Yang; Yazheng Li; Zhaoji Shi; W. E. Abd Allah; El‐Sayed E. A. El‐Sobky; Hui Wei; Jiaen Zhang; Yakov Kuzyakov (Global Change Biology, 2024)
More than half of the world's population is nourished by crops fertilized with synthetic nitrogen (N) fertilizers. However, N fertilization is a major source of anthropogenic emissions, augmenting the carbon footprint (CF). To date, no global quantification of the CF induced by N fertilization of the main grain crops has been performed, and quantifications at the national scale have neglected the CO 2 assimilated by plants. A first cradle‐to‐grave life cycle assessment was performed to quantify the CF of the N fertilizers' production, transportation, and application to the field and the uses of the produced biomass in livestock feed and human food, as well as biofuel production. We quantified the direct and indirect inventories emitted or sequestered by N fertilization of main grain crops: wheat, maize, and rice. Grain food produced with N fertilization had a net CF of 7.4 Gt CO 2 eq. in 2019 after excluding the assimilated C in plant biomass, which accounted for a quarter of the total CF. The cradle (fertilizer production and transportation), gate (fertilizer application, and soil and plant systems), and grave (feed, food, biofuel, and losses) stages contributed to the CF by 2%, 11%, and 87%, respectively. Although Asia was the top grain producer, North America contributed 38% of the CF due to the greatest CF of the grave stage (2.5 Gt CO 2 eq.). The CF of grain crops will increase to 21.2 Gt CO 2 eq. in 2100, driven by the rise in N fertilization to meet the growing food demand without actions to stop the decline in N use efficiency. To meet the targets of climate change, we introduced an ambitious mitigation strategy, including the improvement of N agronomic efficiency (6% average target for the three crops) and manufacturing technology, reducing food losses, and global conversion to healthy diets, whereby the CF can be reduced to 5.6 Gt CO 2 eq. in 2100.

Increased and fluctuating phosphorus nutrient availability positively affects the growth of the invasive plant Solidago canadensis - Miaomiao Cui; Bin Yang; Guangqian Ren; Piergiorgio Stevanato; Xue Fan; Ping Huang; Jianfan Sun; Daolin Du (Flora, 2023)

A review of plants strategies to resist biotic and abiotic environmental stressors - Mohsin Nawaz; Jianfan Sun; Samina Shabbir; Wajid Ali Khattak; Guangqian Ren; Xiaojun Nie; Yanwen Bo; Qaiser Javed; Daolin Du; Christian Sonne (Science of The Total Environment, 2023)

Soil pollution and the invasion of congener Sphagneticola in crop lands - Qaiser Javed; Jianfan Sun; Susan Rutherford; Juan Li; Babar Iqbal; Yan Xiang; Guangqian Ren; Feng He; Linxuan Pan; Yanwen Bo; Wajid Ali Khattak; Daolin Du (Journal of Environmental Management, 2023)

Soil carbon sequestration in paddy field and its simultaneous mineralization to supply available nutrients for the crops are affected by no-tillage with straw management: A meta-analysis - Xing Liu; Zhaoji Shi; Hui Bai; Jiaen Zhang; Daolin Sun; Yuting Chen (Applied Soil Ecology, 2023)

Polyaspartic acid assisted-phytoremediation of cadmium-contaminated farmland: Phytoextraction efficiency, soil quality, and rhizosphere microbial community - Yanwei Liu; Juanjuan Zhou; Daolin Sun; Haifeng Chen; Junhao Qin; Guikui Chen; Rongliang Qiu (Science of The Total Environment, 2023)

Study on the Wind and Wave Environmental Conditions of the Xisha Islands in the South China Sea - Ze Sun; Mengchun Bian; Jun Ding; Jiarui Liu; Haicheng Zhang; Daolin Xu (Journal of Marine Science and Engineering, 2022)
Wind and waves are the main factors of environmental loading on ships and offshore structures. Thus, detailed understanding of wind and wave conditions can improve the design and maintenance of these structures. This paper developed a validated long-term wind and wave hindcast database covering the recent 32 years from 1988 to 2019. The spatial distribution of wind and wave characteristics for the whole Xisha Islands’ domain were analyzed. Frequency and directional distributions of wind speeds and significant wave heights were investigated at several locations around typical islands. Extreme value models were used to estimate the wind speed for 100-year return levels, whereas environmental contour approaches were utilized to establish the extreme sea-state parameters for 50- and 100-year return periods. It was found that the Weibull distribution was better fitted to the significant wave heights of the Xuande Atoll’s sites in the open sea, while the exponential Weibull distribution provided a better fit at the Yongle Atoll’s sites where waves are sheltered.

Indigenous PGPB Inoculant from Qinghai-Tibetan Plateau Soil Confer Drought-Stress Tolerance to Local Grass Poa annua - Yan Li; Min He; Yizhou Du; Xiupu Wang; Hui Zhang; Zhicong Dai; Justin S. H. Wan; Jiquan Sun; Congyan Wang; Daolin Du (International Journal of Environmental Research, 2022)

Invasive Alternanthera philoxeroides has performance advantages over natives under flooding with high amount of nitrogen - Jianfan Sun; Qaiser Javed; Yizhou Du; Ahmad Azeem; Adeel Abbas; Babar Iqbal; Yuhan He; Yan Xiang; Daolin Du (Aquatic Ecology, 2022)

Growth prediction of Alternanthera philoxeroides under salt stress by application of artificial neural networking - Qaiser Javed; Ahmad Azeem; Jianfan Sun; Ikram Ullah; Daolin Du; Muhammad Ali Imran; Muhammad Imran Nawaz; Hassan T. Chattha (Plant Biosystems, 2022)

Evaluation of the allelopathic effects of leachate from an invasive species (Wedelia triobata) on its own growth and performance and those of a native congener (W. chinensis) - Muhammad Saif Ullah; Jianfan Sun; Susan Rutherford; Ikram Ullah; Qaiser Javed; Ghulam Rasool; Muhammad Ajmal; Daolin Du (Biological Invasions, 2021)

The anther-specific CYP704B is potentially responsible for MSG26 male sterility in barley - Juan Qi; Fei Ni; Xiao Wang; Meng Sun; Yu Cui; Jiajie Wu; Allan Caplan; Daolin Fu (Theoretical and Applied Genetics, 2019)